(untitled) (Journal of Governance and Development (JGD), 2016)
The financial management of individuals varies around the world, with rapid economic growth there is an alarming increase in the value of products and services that challenge people who have poor financial management. However, this requires individuals to manage their financial resources through appropriate saving behaviour. This paper investigates psychosocial and behavioural factors influencing consumers’ intention to save money for educational purposes. A web based survey was used to collect data from 174 individuals in Malaysia. An extended theory of planned behaviour was used to model intention to engage in savings behaviour. Research hypotheses were constructed regarding the influence of attitudes, subjective norm and, perceived behavioural control to information exposure and current engagement in saving behaviour. Engagement in saving behaviour and active information on funds conservation predicted intention to save. However, there exposure to information was not implicated and subjective norms and perceptions of control predicted intention to save but attitudes towards saving did not.